Screen Time Exposure and Language Development in Indonesian Children Under Five: A Comprehensive Analysis of Risk Factors and Impacts - Amanda, Vita; Najmah Shareeff (HM Publisher, 2024)
Introduction: The pervasive use of digital devices has raised concerns about the impact of screen time on early childhood development, particularly language skills. This study investigates the relationship between screen time exposure and language development in Indonesian children under five, while also analyzing the influence of socio-demographic and environmental risk factors. Methods: A cross-sectional study was conducted involving 300 Indonesian children aged 1 to 5 years. Parents completed questionnaires on socio-demographics, screen time habits, and their child's language development (assessed using the Indonesian Early Language Development Scale - IELDS). Statistical analyses included descriptive statistics, correlation analysis, and multiple regression to identify predictors of language delay. Results: Increased screen time was significantly correlated with lower scores on the IELDS, indicating delayed language development. Children with higher screen time were more likely to exhibit delays in expressive language, receptive language, and overall communication skills. Socio-economic status, parental education, and home language environment also emerged as significant predictors of language outcomes. Conclusion: This study provides compelling evidence for the negative association between screen time and language development in young Indonesian children. The findings underscore the importance of limiting screen time and promoting language-rich interactions during the critical early years.